Who Seek Homeopathic Treatment? - Elahee, Sheikh Faruque; Rahman, Md Mizanur; Rahman, Md Mahfuzar; Hossain, Shaila; Zaki, Mahbub (Bangladesh Medical Journal, 2009)
Homeopathy, or homeopathic medicine, is a holistic system of treatment and is based on the idea that substances that produce symptoms of sickness in healthy people will have a curative effect when given in very dilute quantities to sick people who exhibit those same symptoms. Homeopathic physicians seek to cure their patients on the physical, mental and emotional levels, and each treatment is tailored to a patient's individual needs. Considering these ideas a cross sectional study was conducted in Dhaka city from March to July, 2008 to determine the characteristics of patients seeking homeopathic treatment. A sample of 250 patients was selected for interview for the study. About one third (31%) of the patients prefer homeopathic treatment and the rest also take other treatments like Allopathic, Ayurbedic and Unani. Majority of the patients chose homeopathic treatment as it has long lasting cure (54%), low cost (27%) and no side effect (25%). The common diseases for which homeopathic treatment was sought were skin diseases (16%), gastrointestinal diseases (15%), genital diseases (14%), ENT diseases (13%) and musculo-skeletal diseases (12%). About 76% patients had previous experience of homeopathic treatment, while 24% received it for the first time. Bi-variate analysis revealed that young age, unmarried and higher income groups of patients were found to be more regular in receiving homeopathic treatment than the older, married and low income groups (p<0.05). Though the study finding did not generalize the medicare system of Bangladesh, but it need to be integrated into the conventional medicine to achieve health for all. Keywords: Homeopathic treatment, characteristics of patients, family income, common diseases, Bangladesh. DOI: 10.3329/bmj.v37i2.3590 Bangladesh Medical Journal 37(2) 2008 37-40